2021
DOI: 10.2147/jpr.s303930
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Minimally Invasive Transforaminal Lumbar Interbody Fusion for Highly Migrated Lumbar Disc Herniation

Abstract: Objective To describe minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) for highly migrated lumbar disc herniation (LDH) and assess its clinical outcomes. Patients and Methods This research retrospectively assessed 25 patients who were diagnosed with one-segmental highly migrated LDH and underwent MIS-TLIF in Peking University First Hospital from June 2015 to September 2019. Demographic data, perioperative parameters, complications, recurrence, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…It implied that the pain outcome of MISTLIF was independent of choice of anaesthesia. 20,21 Mean blood loss reported in our study was 109.64±110.45 ml whereas, Habib et al recorded mean blood loss of 163 ml in MIS TLIF versus 366.8 ml in open TLIF. Schwender et al in his study reported estimated blood loss of 140ml done in general anaesthesia.…”
Section: Discussionmentioning
confidence: 47%
“…It implied that the pain outcome of MISTLIF was independent of choice of anaesthesia. 20,21 Mean blood loss reported in our study was 109.64±110.45 ml whereas, Habib et al recorded mean blood loss of 163 ml in MIS TLIF versus 366.8 ml in open TLIF. Schwender et al in his study reported estimated blood loss of 140ml done in general anaesthesia.…”
Section: Discussionmentioning
confidence: 47%
“…This shows that the pain improvement in MIS TLIF is independent of the type of anesthesia given. 22,25 In our study we had 11.5% incidence of post operative urinary retention while the incidence of nausea/vomiting was 7%. McLain et al had higher incidence of nausea in general anesthesia group and lower incidence of urinary retention in spinal anesthesia group.…”
Section: Discussionmentioning
confidence: 59%
“…It is not only possible to preserve the posterior paraspinal muscles with UBE technique, but the arthroscope can also be inserted directly between the two endplates to observe the process of endplate preparation, which can be visualized and magnified. 3 Wang et al 8 used TLIF to evaluate the lumbar fusion results of 25 patients with lumbar disk herniation using VAS and ODI, and the clinical results were satisfactory after 1 year of follow-up. In this study, the estimated surgical blood loss and hospital stay were lower in the UBEIF group than in the TLIF group ( P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…There are many advantages to minimally invasive surgical techniques over traditional surgery, including surgical trauma, blood loss, postoperative recovery, length of stay, and cost. [5][6][7][8] Unilateral biportal endoscopic technique (UBEIF) is observed and operated through 2 channels via small cuts, where one channel is observed and the other channel is operated without interfering with each other. In addition, instruments for arthroscopic 30°and conventional spinal instruments were used, with the advantage of excellent magnification, economy, and visualization.…”
mentioning
confidence: 99%